Use of a Tendon/Ligament Cell Sheet with Mesenchymal Stem Cells and Cyclic Stretch Stimulus for Tendon / Ligament Tissue Restoration / Yasuyuki Morita...[et al.] - Yasuyuki, Morita; Fuga, Matsubara; Matsubara, Toku; Yang, Ju (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
It can be relatively difficult for damaged tendon or ligament tissue to heal perfectly due to the inability to self-cure. Therefore, tendon and ligament tissue engineering has been used as a restorative method. Perfect tissue restoration, however, has yet to be achieved. In other research, cell sheets have been applied to various different types of tissues and organs for regeneration. In this study, we attempted to fabricate a tendon/ligament cell sheet for use in tissue engineering. Firstly, human bone marrow mesenchymal stem cells (hBMSCs), which have excellent proliferative abilities, were harvested and formed into a cell sheet. Then, a cyclic stretching stimulus was applied to the hBMSC sheet to enhance cell differentiation into tendon/ligament cells. The results showed that the work was successful in promoting differentiation, resulting in a tendon/ligament cell sheet. These results suggest that this method is effective for tendon/ligament tissue engineering.